PENGARUH BRAND REPUTATION DAN BRAND CREDIBILITY TERHADAP BRAND LOYALTY : Studi pada Followers Instagram sekaligus yang menjadi Member Aplikasi Fore Coffee di Indonesia - Fathya Shalmasyah, - (2023)
This study aims to obtain an overview and influence of brand reputation, brand credibility on brand loyalty on Instagram followers who are members of the Fore Coffee application. This research uses descriptive and verification methods with a quantitative approach. The population in this study totaled 154,000 Instagram followers with a sample of 200 respondents who were both followers and members of the Fore Coffee application using a purposive sampling technique. The data were processed statistically using the Structural Equation Modeling (SEM) method. The findings in this study found that in terms of brand reputation, brand credibility and brand loyalty, they were in a fairly good category. Brand reputation and brand credibility have a positive and significant influence on brand loyalty, this is indicated by the critical ratio value which is greater than the minimum value, meaning that there is a positive and significant influence between brand reputation and brand credibility variables on brand loyalty simultaneously. It can be assumed that the better the company pays attention to brand reputation and brand credibility, the better brand loyalty will be for the company. The result of the highest contribution given by the brand reputation variable in forming brand loyalty is image and the lowest in forming brand loyalty is identity. The dimension of brand credibility that has the highest contribution in forming brand loyalty is Attractivenes and the one that has the lowest in forming brand loyalty is expertise. These findings indicate that the application of brand reputation and brand credibility by Fore Coffee will encourage brand loyalty to followers and at the same time become members of the Fore Coffee application. Keywords: Brand Reputation, Brand Credibility, Brand Loyalty.